Copper and Zinc status in women with unexplained infertility - AL-Saraf M. Khulood; AL-Asadi A. Faris; A.Hussain saad (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2005)
Zinc is the most widely studied element in term of fertility in both men and women; and zinc deficiency was reported to be associated with infertility. This prospective, randomized controlled study was conducted in the Infertility and IVF center, AL-Samarai Hospital Baghdad-Iraq, to evaluate the level of Cu/Zn ratio in the serum of women with unexplained infertility. Serum levels of copper and zinc were evaluated in twenty six women with unexplained infertility, and in twenty normal women served as control, using atomic absorption spectrophotometer. serum Zn levels were significantly lower compared to control group (6.63 mol/L ± 0.24 VS 9.0 mol/L ± 0.9, P= 0.01), serum Cu levels were significantly higher compared to controls (10.92 mol/L ± 0.4 VS 7.81 mol/L ± 0.38, P=0.01), Cu/Zn ratio was higher in infertile group (1.65 ± 0.014 VS 0.86 ± 0.011, P= 0.02). From these results it was concluded that the increase in Cu/Zn ratio may have an important etiological role in the pathogenicity of unexplained infertility, and therapeutic intervention in this respect may be beneficial in the treatment of this condition.